EVALUASI TEKNIS KONSEP PADA DESAIN ALAT PENEBAR PUPUK BUTIRAN - Editiya Putra Utama; Jenal Sodikin; Tarigan, Roy Aries Permana; Mohammad Nurhilal; Cecep Deni Mulyadi; Ulikaryani (Politeknik Negeri Cilacap, 2024)
The technique of spreading fertilizer on rice plants is an important part of equalizing land fertility. In general, farmers use their hands to spread granular fertilizer. The spreading process results in an irregular distribution of fertilizer and also takes a relatively long time. The aim of this research is to design a granular fertilizer spreader based on a technical evaluation of the concept. The Pahl and Beitz design method became a theoretical reference in finalizing the design of the granular fertilizer spreader form. Working drawings are prepared based on ISO standards using Solidwork 2018 software. Based on the results of the technical evaluation of the concept, the design of the granular fertilizer spreader is composed of thirty-three constituent components.